Students Expectations of Higher Education at Indonesian Public and Private Universities - Novi Irwansyah (Journal of Education Research, 2023)
Understanding student expectations about offering the best educational experience is crucial in the education business. As a result, customer-oriented methods to management are widely used at higher education institutions (HEI). The customer-oriented approach to students as customers has been examined from several perspectives in academic literature. However, it has rarely been addressed in terms of comparing public and private universities. The current study attempted to evaluate disparities in student expectations of their educational experience at public and private colleges using a student-customer orientation questionnaire (SCOQ). The sample comprised of 238 undergraduate students from Indonesian universities. The study discovered intriguing distinctions between university kinds in terms of graduation, curriculum design, communication with service staff, classroom studies, individual studies, and course design.